A crack in the edge of the world the great American earthquake of 1906 - Winchester, Simon (Penguin Books, 2006)
Winchester brings his storytelling abilities, as well as his understanding of geology, to the extraordinary San Francisco Earthquake, exploring not only what happened in northern California in 1906 that leveled a city symbolic of America's relentless western expansion, but what we have learned since about the geological underpinnings that caused the earthquake. He also positions the quake's significance along the earth's geological timeline and shows the effect it had on the rest of 20th-century California and American history.--From publisher description